A Critique of the Literary School of Critical Realism in Iran (Based on the Stories of “Farsi Shekar Ast/Persian is Sugar” and “Gileh Mard”) - Nahid Akbarzadeh; Janolah Karimi Motahhar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The late eighteenth and early nineteenth centuries were the time for the formation of new schools of art in Europe. The rise of realism was the result of fundamental changes in the understanding of the world and a fundamental revision of the relationship between man and the world. In post-labor Europe, the approach of writers and poets, previously based on reason (classics) or on individual fantasies (romantics), changes dramatically and the individual's confrontation with his surroundings became the main subject of this literary school. Realism portrayed the collective feelings and realities around it. This literary school was divided into different branches, including magical realism, bourgeois, critical, surrealism, and so on. The traces of this literary school are also evident in the works of Iranian writers. Iran underwent fundamental political, social, and cultural changes in the late nineteenth and early twentieth centuries. Therefore, literary movements in Iran have undergone important changes. Following the Constitutional Revolution, land reform, the entry of the printing industry, translation of literary works, etc., the language and style of writing in Iran changed. Folk, fluent, simple, and humorous language replaced the court and official language. Short stories, footnotes, and socio-historical novels replaced didactic literature and mystical theology.